Morphotectonic Analysis of the East Manus Basin, Papua New Guinea - Dyriw, Nicholas J.; Bryan, Scott E.; Richards, Simon W.; Parianos, John M.; Arculus, Richard J.; Gust, David A. (Frontiers in Earth Science, 2021)
Backarc basin systems are important sites of extension leading to crustal rupture where basin development typically occurs in rifting phases (or stages) with the final successful stages identified by the formation of spreading ridges and new oceanic crust. The East Manus Basin is a young (<1 Ma), active, rapidly rifting backarc basin in a complex tectonic setting at the confluence of the oblique convergence of the Australian and Pacific plates. Here we undertake the first comprehensive spatial-temporal morphotectonic description and interpretation of the East Manus Basin including a link to the timing of, and tectonic controls on, the formation of seafloor massive sulfide mineralization. Key seafloor datasets used in the morphotectonic analysis include multi-resolution multibeam echosounder seafloor data and derivatives. Morphotectonic analysis of these data defines three evolutionary phases for the East Manus Basin. Each phase is distinguished by a variation in seafloor characteristics, volcano morphology and structural features: Phase 1 is a period of incipient extension of existing arc crust with intermediate to silicic volcanism; Phase 2 evolves to crustal rifting with effusive, flat top volcanoes with fissures; and Phase 3 is a nascent organized half-graben system with axial volcanism and seafloor spreading. The morphotectonic analysis, combined with available age constraints, shows that crustal rupture can occur rapidly (within ∼1 Myr) in backarc basins but that the different rift phases can become abandoned and preserved on the seafloor as the locus of extension and magmatism migrates to focus on the ultimate zone(s) of crustal rupture. Consequently, the spatial-temporal occurrence of significant Cu-rich seafloor massive sulfide mineralization can be constrained to the transition from Phase 1 to Phase 2 within the East Manus Basin. Mineralizing hydrothermal systems have utilized interconnected structural zones developed during these phases. This research improves our understanding of the early evolution of modern backarc systems, including the association between basin evolution and spatial-temporal formation of seafloor massive sulfide deposits, and provides key morphotectonic relationships that can be used to help interpret the evolution of paleo/fossilized backarc basins found in fold belts and accreted terrains around the world.